A plastic alloy material containing modified recycled resin and its preparation method and application

By mixing the modified glass fiber and other auxiliary agents and squeezed out, prepare a plastic alloy material containing a modified recycling resin, solve the problem of unsatisfactory performance of the existing recycling alloy mechanics, and achieve high -quality cycle utilization And high -value recycling.

CN119019842BActive Publication Date: 2025-01-28GUANGDONG BOSHIDA NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411506150.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing PET recycling materials and PA66 recycling materials process routes adopt direct capacity modification, resulting in unsatisfactory mechanical properties of the recycling alloy.

Method used

By mixing the modified glass fiber and antioxidant, flow modifiers, branches increase solvents, RPET resin slices, and car water tanks to recycle PA66 material, and use dual screw extruders to squeeze out Plastic alloy materials for sexual recycling resin.

Benefits of technology

This method not only improves the mechanical properties of plastic alloy materials, is close to the performance of PA66 new materials native alloy materials, but also realizes the high -value use of recycling and regeneration of PA66 and PET, which is in line with national carbon neutralization policies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a plastic alloy material containing modified recycled resin and a preparation method and application thereof, and relates to the technical field of plastic alloy materials. The preparation method of the plastic alloy material containing modified recycled resin of the invention comprises the following steps: after blending black sand and modified glass fiber, mixing with antioxidant, flow modifier, grafting solubilizer, rPET resin slices, and PA66 material recycled from automobile water tank, extruding, and obtaining plastic alloy material; the application uses rPET with lower cost to partially replace PA66, and after chain extension, viscosity enhancement and glass fiber reinforcement modification, a modified product with performance comparable to that of new PA66 material can be obtained, and is applied to the furniture field, realizing the high-value utilization of recycling and regeneration of PA66 and PET.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic alloy materials, and in particular to a plastic alloy material containing modified recycled resin and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate is a widely used thermoplastic polyester. It not only has good chemical resistance, friction resistance, creep resistance, fatigue resistance, resistance to weak acids and organic solvents, and electrical insulation properties, but also has the characteristics of high strength and easy molding. Therefore, it is widely used and its usage is increasing. The market demand for polyester bottle flakes (PET) products in my country has shown a steady growth trend. However, due to the varying degrees of degradation of PET bottle flakes after use, recycled PET (rPET) cannot directly meet the bottle grade requirements. Currently, rPET is mainly used in polyester fiber production, which greatly reduces the high-value recycling and reuse of rPET. The recycling and reuse of nylon 66 (PA66) plastic has become more and more advantageous than the original PA66.

[0003] When used as plastic, polyethylene terephthalate has the disadvantages of slow crystallization speed under processing molds (70-110℃), long molding cycle, rough surface, easy deformation and poor impact resistance, which limits its wide application. PA66 and polyethylene terephthalate have similar melting points, but since the blend of PA66 and polyethylene terephthalate is a crystallization and phase separation system, it is very important to improve their compatibility. The most effective way is to use the reactive functional groups such as terminal carboxyl, terminal hydroxyl, and terminal amino groups in the polymer to make them undergo exchange or polycondensation reactions, forming copolymers at the polymer interface to act as compatibilizers, reduce the surface tension of the two-phase interface, increase the interphase adhesion, and improve the performance. However, the existing recycled material process route is direct volume modification, because the recycled material has different degrees of degradation, and the direct volume modification into alloy mechanical properties is not ideal. Summary of the invention

[0004] The purpose of the present invention is to provide a plastic alloy material containing modified recycled resin and a preparation method and application thereof, so as to solve the following technical problems:

[0005] The existing process routes for recycled PET and PA66 materials use direct volume expansion and modification. However, since the recycled materials are degraded to varying degrees, the mechanical properties of the alloys produced by direct volume expansion and modification are not ideal.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps: blending black sand and modified glass fiber, then mixing with an antioxidant, a flow modifier, a grafting solubilizer, rPET resin slices, and PA66 material recycled from automobile water tanks, and extruding to obtain a plastic alloy material;

[0008] The preparation method of modified glass fiber comprises the following steps:

[0009] S1: γ-aminopropyltriethoxysilane, succinic anhydride, and N,N-dimethylformamide component 1 are added to a reaction kettle and dispersed evenly, glass fiber, N,N-dimethylformamide component 2, and deionized water are mixed and added to the reaction kettle, the temperature is controlled at 40-50°C, the reaction is kept warm for 3-6 hours, centrifuged, washed with alcohol, and dried to obtain component 1;

[0010] S2: Add adipic acid, hexamethylenediamine and anhydrous ethanol into a reaction kettle and disperse them evenly. Control the temperature at 25-35°C, keep the temperature for reaction for 0.5-1h, filter and wash with alcohol to obtain component 2.

[0011] S3: In a nitrogen atmosphere, add component 1 and component 2 into a reaction kettle and disperse them evenly. Control the temperature at 210-220°C, keep the reaction warm for 2-4 hours, wash with formic acid, and dry to obtain modified glass fiber.

[0012] Preferably, N,N-dimethylformamide component one and N,N-dimethylformamide component two in S1 are both N,N-dimethylformamide; the addition ratio of γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide component one, glass fiber, N,N-dimethylformamide component two, and deionized water is 5-8g: 1-1.1g: 50-100mL: 10g: 10-20mL: 10-20mL.

[0013] Preferably, the addition ratio of adipic acid, hexamethylenediamine and anhydrous ethanol in S2 is 1 g: 0.6-0.8 g: 10-20 mL.

[0014] Preferably, the addition ratio of component one to component two in S3 is 1g:3-6g.

[0015] Preferably, the modified glass fiber accounts for 26.2-38.8% of the total mass of the plastic alloy material.

[0016] Preferably, during the preparation of the plastic alloy material, the extrusion temperature of the twin-screw extruder is 240-265° C. and the rotation speed is 350-400 rpm.

[0017] Preferably, the preparation method of automobile radiator recycled PA66 material comprises the following steps: adding automobile radiator crushed material, diepoxy group chain extender EP, and antioxidant into a twin-screw extruder for extrusion and granulation to obtain automobile radiator recycled PA66 material; automobile radiator recycled PA66 material accounts for 37.3-45.9% of the total mass of the plastic alloy material.

[0018] Preferably, the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; the automobile radiator recycled PA66 material includes the following raw materials in weight percentage: 1-3% diepoxy group chain extender EP, 0.1-0.5% antioxidant, and the remainder is automobile radiator crushed material; the sum of the weight percentages is 100%.

[0019] Preferably, the extrusion temperature of the twin-screw extruder during the preparation of the PA66 material recycled from automobile water tanks is 240-270°C.

[0020] Preferably, the preparation method of automobile radiator material scraps comprises the following steps: coarse sorting of automobile radiator material to remove large impurities, magnetic metals, non-magnetic metals, manual sorting, wet crushing, hot alkaline water washing to remove oil stains, drying, electrostatic sorting, infrared and color fine sorting, and warehousing and homogenization to obtain automobile radiator material scraps.

[0021] Preferably, the preparation method of rPET resin chips comprises the following steps: adding PET bottle recycled material, pyromellitic anhydride, phthalic anhydride compounded chain extender, and antioxidant into a twin-screw extruder for extrusion and granulation to obtain rPET resin chips; the rPET resin chips account for 17.4-21.4% of the total mass of the plastic alloy material.

[0022] Preferably, the antioxidant used in the preparation process of rPET resin chips is a hindered phenol antioxidant or a phosphite antioxidant; the rPET resin chips include the following raw materials in weight percentage: 0.1-0.3% of pyromellitic anhydride, 0.1-0.3% of phthalic anhydride compound chain extender, 0.1-0.5% of antioxidant, and the remainder is PET bottle recycled material, and the sum of the weight percentages is 100%.

[0023] Preferably, the extrusion temperature of the twin-screw extruder during the preparation of the rPET resin chips is 230-260°C.

[0024] Preferably, the preparation method of PET bottle recycled materials comprises the following steps: roughly sorting the recycled PET bottle plastics to remove large impurities, magnetic metals, non-magnetic metals, manual sorting, wet crushing, hot alkaline water washing to remove oil stains, drying, electrostatic sorting, infrared and color fine sorting, and warehousing and homogenization to obtain PET bottle recycled materials.

[0025] Preferably, the preparation method of the grafting solubilizer comprises the following steps: adding PP, maleic anhydride, initiator and antioxidant into a twin-screw extruder for extrusion and granulation to obtain the grafting solubilizer; the grafting compatibilizer accounts for 3.5-6.0% of the total mass of the plastic alloy material.

[0026] Preferably, the initiator is dicumyl peroxide; the antioxidant used in the preparation process of the grafting solubilizer is a hindered phenol antioxidant or a phosphite antioxidant; the grafting solubilizer comprises the following raw materials in weight percentage: 5-10% maleic anhydride, 0.1-0.5% initiator dicumyl peroxide, 0.1-0.5% antioxidant, and the balance is PP; the sum of the weight percentages is 100%.

[0027] Preferably, the extrusion temperature of the twin-screw extruder during the preparation of the grafting solubilizer is 180-200°C.

[0028] Preferably, the flow modifier is PP 6102; the flow modifier accounts for 0.2-0.4% of the total mass of the plastic alloy material.

[0029] Preferably, the antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; the antioxidant accounts for 0.1-0.2% of the total mass of the plastic alloy material.

[0030] Preferably, the black sand is organic carbon black modified by a coupling agent; the black sand accounts for 0.08-0.1% of the total mass of the plastic alloy material.

[0031] Preferably, the method for preparing organic carbon black comprises the following steps: after blending the solvent and the coupling agent, adding carbon black, controlling the temperature at 60-70° C., keeping the temperature for reaction for 10-30 min, filtering, extracting and drying to obtain organic carbon black.

[0032] Preferably, the coupling agent is a silane coupling agent; the solvent is a mixture of isopropanol and water in a volume ratio of 3:1; the addition ratio of solvent: coupling agent: carbon black is 200-300 mL: 2.5-7.5 g: 100 g.

[0033] Preferably, the coupling agent is any one of a titanate coupling agent and an aluminate coupling agent; the solvent is isopropyl ester; and the addition ratio of solvent: coupling agent: carbon black is 200-300 mL: 2.5-7.5 g: 100 g.

[0034] A plastic alloy material containing modified recycled resin is made by any one of the above preparation methods.

[0035] A plastic alloy material containing modified recycled resin is used in the field of furniture.

[0036] Preferably, the field of furniture includes seat supports.

[0037] Beneficial effects of the present invention:

[0038] (1) This application first extends the chain and increases the viscosity of recycled PET bottle materials and automobile radiator materials to obtain rPET resin slices and automobile radiator recycled PA66 materials, and uses flow modifiers and grafting solubilizers to increase the capacity and modify them. This application uses lower-cost rPET to partially replace PA66, and adds modified glass fiber prepared in this application to prepare a new alloy material, which is close to the original alloy material of PA66 new material in performance. The prepared plastic alloy is applied to the furniture field, realizing the high-value recycling of PA66 and PET. The modified recycling process route of this application realizes high-quality recycling of two general-purpose engineering plastics, which is in line with the national carbon neutrality policy. The plastic alloy material prepared in this application is used to prepare high-performance office chairs with excellent mechanical properties.

[0039] (2) The present application first uses succinic anhydride to carboxylate γ-aminopropyltriethoxysilane to obtain a terminal carboxyl silane coupling agent, and uses the hydrolysis reaction of the terminal carboxyl silane coupling agent to react with the hydroxyl groups on the surface of the glass fiber to graft carboxyl groups on the surface of the glass fiber to obtain component one; the present application then uses in-situ polymerization to graft amide polymers on the surface of the carboxylated glass fiber to obtain modified glass fiber. The present application uses chemical grafting to coat the surface of the glass fiber with organic materials to form a resin coating on the surface of the glass fiber, which not only improves the dispersibility of the glass fiber in the matrix and improves the interfacial bonding strength between the glass fiber and the matrix, but also improves the tensile strength, flexural strength and notched impact strength of the composite material.

[0040] This application utilizes various polar groups on the surface of carbon black, such as hydroxyl, carboxyl, carbonyl, and lactone groups, to bond the inorganic end of the coupling agent molecule to the hydroxyl hydrogen atoms on the surface of carbon black, and organically modify the carbon black to obtain organic carbon black. The coupling agent coated on the surface of carbon black forms a barrier layer, which effectively reduces the attraction and cohesion between carbon black particles. At the same time, the flexible segment on the surface of carbon black has good compatibility with the matrix. When blended with modified glass fiber, the organic long chain fully and effectively infiltrates and coats the carbon black particles with the modified glass fiber surface resin through the van der Waals force between molecules and the physical entanglement or cross-linking of the polymer chain. The modified glass fiber prepared in this application is blended with organic carbon black and then added to the material. During the molding process of the prepared composite material, the interfacial stress and strain generated by the cooling and shrinkage of the resin induces the crystallization of the matrix resin cross-linked with the resin coated on the surface of the glass fiber, refines the resin crystallization, and effectively adjusts the structural properties of the matrix resin. DETAILED DESCRIPTION

[0041] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1 The preparation method of the grafting solubilizing agent comprises the following steps:

[0043] 93.4 g PP, 6 g maleic anhydride, 0.3 g initiator dicumyl peroxide, and 0.3 g antioxidant 1010 were added into a twin-screw extruder for extrusion at an extrusion temperature of 180° C. and a rotation speed of 120 rpm to obtain a grafting solubilizer.

[0044] Example 2 The preparation method of organic carbon black comprises the following steps:

[0045] After mixing 180 mL of isopropanol, 60 mL of water, and 5 g of γ-aminopropyltriethoxysilane, 100 g of carbon black (particle size 80 nm) was added, the temperature was controlled at 70°C, the reaction was kept warm for 10 minutes, and then filtered, extracted, and dried to obtain organic carbon black.

[0046] Example 3 The preparation method of PA66 material recycled from automobile water tank comprises the following steps:

[0047] A1: Roughly sort the automobile radiator materials to remove large impurities, magnetic metals, non-magnetic metals, manually sort, wet crush, hot alkaline water washing to remove oil stains, dry, electrostatic sorting, infrared and color fine sorting, and warehousing and homogenization to obtain automobile radiator material scraps;

[0048] A2: 98g of automobile radiator crushed material, 1.8g of diepoxy group chain extender EP, and 0.2g of antioxidant 1010 were added into a twin-screw extruder for extrusion. The extrusion temperature of the twin-screw extruder was 240°C, the rotation speed was 400rpm, and granulation was performed to obtain automobile radiator recycled PA66 material.

[0049] Example 4 The preparation method of rPET resin chips comprises the following steps:

[0050] B1: Roughly sort the recycled plastics from PET bottles to remove large impurities, magnetic metals, non-magnetic metals, manually sort, wet crush, wash with hot alkaline water to remove oil stains, dry, electrostatically sort, infrared and color fine sort, and store in a warehouse for homogenization to obtain recycled PET bottles;

[0051] B2: 99.45 g of PET bottle recycled material, 0.15 g of pyromellitic anhydride, 0.2 g of phthalic anhydride compound chain extender, and 0.2 g of antioxidant were added into a twin-screw extruder for extrusion at an extrusion temperature of 250° C. and a rotation speed of 60 rpm to obtain rPET resin chips.

[0052] Example 5 The preparation method of modified glass fiber comprises the following steps:

[0053] S1: 5 g of γ-aminopropyltriethoxysilane, 1 g of succinic anhydride, and 50 mL of N,N-dimethylformamide were added to a reactor and dispersed evenly. 10 g of glass fiber (short cut length 4 mm, single fiber diameter 13 um), 10 mL of N,N-dimethylformamide, and 10 mL of deionized water were mixed and added to the reactor. The temperature was controlled at 40°C, and the reaction was kept warm for 3 h. The mixture was centrifuged, washed with alcohol, and dried to obtain component 1.

[0054] S2: Add 1 g adipic acid, 0.6 g hexamethylenediamine and 10 mL anhydrous ethanol into a reaction kettle and disperse evenly. Control the temperature at 25°C, keep the reaction warm for 0.5 h, filter and wash with alcohol to obtain component 2.

[0055] S3: In a nitrogen atmosphere, 1 g of component 1 and 3 g of component 2 were added into a reactor and dispersed evenly. The temperature was controlled at 210°C and the reaction was kept warm for 2 hours. The modified glass fiber was washed with formic acid and dried to obtain the modified glass fiber.

[0056] Example 6 The preparation method of modified glass fiber comprises the following steps:

[0057] S1: 6 g of γ-aminopropyltriethoxysilane, 1.1 g of succinic anhydride, and 70 mL of N,N-dimethylformamide were added to a reactor and dispersed evenly. 10 g of glass fiber (short cut length 4 mm, single fiber diameter 13 um), 10 mL of N,N-dimethylformamide, and 10 mL of deionized water were mixed and added to the reactor. The temperature was controlled at 45°C, and the reaction was kept warm for 4.5 hours. The mixture was centrifuged, washed with alcohol, and dried to obtain component 1.

[0058] S2: Add 1 g of adipic acid, 0.7 g of hexamethylenediamine and 15 mL of anhydrous ethanol into a reaction kettle and disperse evenly. Control the temperature at 30°C, keep the reaction warm for 0.5 h, filter and wash with alcohol to obtain component 2.

[0059] S3: In a nitrogen atmosphere, 1 g of component 1 and 4.5 g of component 2 were added into a reactor and dispersed evenly. The temperature was controlled at 210°C and the reaction was kept warm for 3 hours. The modified glass fiber was washed with formic acid and dried to obtain the modified glass fiber.

[0060] Example 7 The preparation method of modified glass fiber comprises the following steps:

[0061] S1: 8 g of γ-aminopropyltriethoxysilane, 1.1 g of succinic anhydride, and 100 mL of N,N-dimethylformamide were added to a reactor and dispersed evenly. 10 g of glass fiber (short cut length 4 mm, single fiber diameter 13 um), 20 mL of N,N-dimethylformamide, and 20 mL of deionized water were mixed and added to the reactor. The temperature was controlled at 50°C, and the reaction was kept warm for 6 hours. The mixture was centrifuged, washed with alcohol, and dried to obtain component 1.

[0062] S2: 1 g adipic acid, 0.8 g hexamethylenediamine and 20 mL anhydrous ethanol were added into a reaction kettle and dispersed evenly. The temperature was controlled at 35°C and kept for reaction for 1 h. The mixture was filtered and washed with alcohol to obtain component 2.

[0063] S3: In a nitrogen atmosphere, 1 g of component 1 and 6 g of component 2 were added into a reactor and dispersed evenly. The temperature was controlled at 220°C and the reaction was kept warm for 4 hours. The modified glass fiber was washed with formic acid and dried to obtain the modified glass fiber.

[0064] Embodiment 8 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0065] 27.42 g of the modified glass fiber prepared in Example 5 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafting solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, and 45.9 g of the automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0066] Embodiment 9 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0067] 27.42 g of the modified glass fiber prepared in Example 6 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafting solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, and 45.9 g of the automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0068] Embodiment 10 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0069] 27.42 g of the modified glass fiber prepared in Example 7 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafting solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, and 45.9 g of the automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0070] Comparative Example 1 The preparation method of modified glass fiber comprises the following steps:

[0071] 6 g of γ-aminopropyltriethoxysilane, 1.1 g of succinic anhydride, and 70 mL of N,N-dimethylformamide were added to a reactor and dispersed evenly. 10 g of glass fiber (short cut length 4 mm, single fiber diameter 13 um), 10 mL of N,N-dimethylformamide, and 10 mL of deionized water were blended and added to the reactor. The temperature was controlled at 45°C, and the reaction was kept warm for 4.5 hours. The mixture was centrifuged, washed with alcohol, and dried to obtain modified glass fiber.

[0072] Comparative Example 2 The preparation method of modified glass fiber comprises the following steps:

[0073] S1: 6 g of γ-aminopropyltriethoxysilane and 70 mL of N,N-dimethylformamide were added to a reactor and dispersed evenly. 10 g of glass fiber (chopped length 4 mm, single fiber diameter 13 um), 10 mL of N,N-dimethylformamide and 10 mL of deionized water were mixed and added to the reactor. The temperature was controlled at 45°C, and the reaction was kept warm for 4.5 hours. The mixture was centrifuged, washed with alcohol and dried to obtain component 1.

[0074] S2: Add 1 g of adipic acid, 0.7 g of hexamethylenediamine and 15 mL of anhydrous ethanol into a reaction kettle and disperse evenly. Control the temperature at 30°C, keep the reaction warm for 0.5 h, filter and wash with alcohol to obtain component 2.

[0075] S3: In a nitrogen atmosphere, 1 g of component 1 and 4.5 g of component 2 were added into a reactor and dispersed evenly. The temperature was controlled at 210°C and the reaction was kept warm for 3 hours. The modified glass fiber was washed with formic acid and dried to obtain the modified glass fiber.

[0076] Comparative Example 3 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0077] 27.42g of the modified glass fiber prepared in Comparative Example 1 and 0.08g of the black sand prepared in Example 2 were blended, and then mixed with 0.2g of antioxidant 1010, 0.4g of flow modifier PP 6102, 5g of the grafting solubilizer prepared in Example 1, 21g of the rPET resin slice prepared in Example 4, and 45.9g of the automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250°C and the rotation speed was 400rpm to obtain a plastic alloy material.

[0078] Comparative Example 4 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0079] 27.42 g of the modified glass fiber prepared in Comparative Example 2 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafting solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, and 45.9 g of the automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0080] Comparative Example 5 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0081] 27.42 g of the modified glass fiber prepared in Example 6 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafted solubilizer prepared in Example 1, 21 g of PET bottle recycled material, and 45.9 g of automobile water tank recycled PA66 material prepared in Example 3 in a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0082] Comparative Example 6 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0083] 27.42 g of the modified glass fiber prepared in Example 6 and 0.08 g of the black sand prepared in Example 2 were blended, and then mixed with 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafting solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, and 45.9 g of automobile water tank material crushed materials in a high-speed mixer, mixed evenly, and extruded by a twin-screw extruder at an extrusion temperature of 250° C. and a rotation speed of 400 rpm to obtain a plastic alloy material.

[0084] Comparative Example 7 A method for preparing a plastic alloy material containing modified recycled resin comprises the following steps:

[0085] 0.08 g of the black sand prepared in Example 2, 0.2 g of antioxidant 1010, 0.4 g of flow modifier PP 6102, 5 g of the grafted solubilizer prepared in Example 1, 21 g of the rPET resin slice prepared in Example 4, 45.9 g of the automobile water tank recycled PA66 material prepared in Example 3, and 27.42 g of the modified glass fiber prepared in Example 6 were put into a high-speed mixer, mixed well, and extruded by a twin-screw extruder. The extrusion temperature of the twin-screw extruder was 250° C. and the rotation speed was 400 rpm to obtain a plastic alloy material.

[0086] Performance Testing

[0087] (1) Tensile strength: The test was carried out according to GB / T 1040-1992 “Plastic Tensile Test Method”, with a tensile speed of 50 mm / min. The test results are shown in Table 1.

[0088] (2) Notched impact strength: The test was conducted in accordance with GB / T 1843-2008 “Determination of cantilever beam impact strength of plastics”. The notch depth was 2.5 mm and the notch tip radius was 0.25 mm. The test results are shown in Table 1.

[0089] (3) Flexural strength and flexural modulus: GB / T 9341-2000 “Test method for flexural properties of plastics” was used for testing. The pressing speed was 2 mm / min. The test results are shown in Table 1.

[0090] Table 1: Statistical table of mechanical properties test data of Examples 8-10 and Comparative Examples 3-7

[0091]

[0092] As can be seen from Table 1, the plastic alloy prepared by adding modified glass fiber to the resin matrix in the present application has excellent mechanical properties; and the present application firstly blends the modified glass fiber with the organic carbon black and then blends it with the resin matrix and other additives, and the organic carbon black is cross-linked with the organic coating layer coated on the surface of the modified glass fiber, which effectively increases the interfacial stress strain induced by the cooling shrinkage of the resin and the crystallization of the matrix resin cross-linked with the resin coated on the surface of the glass fiber, refines the resin crystallization, and effectively adjusts the structural properties of the matrix resin.

[0093] In the present application, the recycled PET bottle recycled materials and automobile radiator materials are respectively chain extended and viscosity increased to obtain rPET resin slices and automobile radiator recycled PA66 materials. The mechanical properties of the plastic alloys obtained by direct volume expansion modification of the existing PET recycled materials and PA66 recycled materials process routes are better.

[0094] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a plastic alloy material containing modified recycled resin, characterized in that: The method comprises the following steps: blending black sand and modified glass fiber, and then mixing with an antioxidant, a flow modifier, a grafting solubilizer, rPET resin slices, and PA66 material recycled from automobile water tanks, and extruding to obtain a plastic alloy material; The preparation method of modified glass fiber comprises the following steps: S1: γ-aminopropyltriethoxysilane, succinic anhydride, and N,N-dimethylformamide component 1 are added to a reaction kettle and dispersed evenly, glass fiber, N,N-dimethylformamide component 2, and deionized water are mixed and added to the reaction kettle, the temperature is controlled at 40-50°C, the reaction is kept warm for 3-6 hours, centrifuged, washed with alcohol, and dried to obtain component 1; S2: Add adipic acid, hexamethylenediamine and anhydrous ethanol into a reaction kettle and disperse them evenly. Control the temperature at 25-35°C, keep the temperature for reaction for 0.5-1h, filter and wash with alcohol to obtain component 2. S3: In a nitrogen atmosphere, add component 1 and component 2 into a reaction kettle and disperse them evenly, control the temperature at 210-220°C, keep the reaction warm for 2-4 hours, wash with formic acid, and dry to obtain modified glass fiber; In S1, the N,N-dimethylformamide component 1 and the N,N-dimethylformamide component 2 are both N,N-dimethylformamide; the addition ratio of γ-aminopropyltriethoxysilane, succinic anhydride, N,N-dimethylformamide component 1, glass fiber, N,N-dimethylformamide component 2, and deionized water is 5-8g: 1-1.1g: 50-100mL: 10g: 10-20mL: 10-20mL; The addition ratio of adipic acid, hexamethylenediamine and anhydrous ethanol in S2 is 1 g: 0.6-0.8 g: 10-20 mL; The addition ratio of component 1 to component 2 in S3 is 1g:3-6g; Modified glass fiber accounts for 26.2-38.8% of the total mass of plastic alloy materials; The preparation method of the automobile water tank recycled PA66 material comprises the following steps: adding automobile water tank crushed material, a diepoxy group chain extender EP, and an antioxidant into a twin-screw extruder for extrusion and granulation to obtain automobile water tank recycled PA66 material; the automobile water tank recycled PA66 material accounts for 37.3-45.9% of the total mass of the plastic alloy material; The preparation method of the rPET resin slice comprises the following steps: adding PET bottle recycled material, pyromellitic anhydride, phthalic anhydride compounded chain extender, and antioxidant into a twin-screw extruder for extrusion and granulation to obtain rPET resin slice; the rPET resin slice accounts for 17.4-21.4% of the total mass of the plastic alloy material; The preparation method of the grafting solubilizer comprises the following steps: adding PP, maleic anhydride, initiator and antioxidant into a twin-screw extruder for extrusion and granulation to obtain the grafting solubilizer; the grafting solubilizer accounts for 3.5-6.0% of the total mass of the plastic alloy material; The black sand is organic carbon black modified by a coupling agent; the black sand accounts for 0.08-0.1% of the total mass of the plastic alloy material.

2. The method for preparing a plastic alloy material containing modified recycled resin according to claim 1, characterized in that: The flow modifier is PP 6102; the flow modifier accounts for 0.2-0.4% of the total mass of the plastic alloy material.

3. The method for preparing a plastic alloy material containing modified recycled resin according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant or a phosphite antioxidant; the antioxidant accounts for 0.1-0.2% of the total mass of the plastic alloy material.

4. A plastic alloy material containing modified recycled resin, characterized in that: Prepared by the preparation method described in any one of claims 1 to 3.

5. A plastic alloy material containing modified recycled resin as claimed in claim 4 is used in the field of furniture.

Citation Information

Patent Citations

  • Method for preparing conductive plastics taking recovered plastics as matrix

    CN101905495A

  • Waste PET (Polyester) heat-proof tackifying and reinforcing composite material and preparation process thereof

    CN103146159A